Activation domains for controlling plant gene expression using designed transcription factors. Issue 6 (22nd March 2013) - Li, Jianquan; Blue, Ryan; Zeitler, Bryan; Strange, Tonya L.; Pearl, Jocelynn R.; Huizinga, David H.; Evans, Steve; Gregory, Philip D.; Urnov, Fyodor D.; Petolino, Joseph F.
Summary: Targeted gene regulation via designed transcription factors has great potential for precise phenotypic modification and acceleration of novel crop trait development. To this end, designed transcriptional activators have been constructed by fusing transcriptional activation domains to DNA‐binding proteins. In this study, a transcriptional activator from the herpes simplex virus, VP16, was used to identify plant regulatory proteins. Transcriptional activation domains were identified from each protein and fused with zinc finger DNA‐binding proteins (ZFPs) to generate designed transcriptional activators. In addition, specific sequences within each transcriptional activation domain were modified to mimic the VP16 contact motif that interacts directly with RNA polymerase II core transcription factors. To evaluate these designed transcriptional activators, test systems were built in yeast and tobacco comprising reporter genes driven by promoters containing ZFP‐binding sites upstream of the transcriptional start site. In yeast, transcriptional domains from the plant proteins ERF2 and PTI4 activated MEL1 reporter gene expression to levels similar to VP16 and the modified sequences displayed even greater levels of activation. Following stable transformation of the tobacco reporter system with transcriptional activators derived from ERF2, GUS reporter gene transcript accumulation was equal to or greater than those derived from VP16 . Moreover, a modified ERF2 domain displayed significantly enhanced transcriptional activation compared with VP16 and with the unmodified ERF2 sequence. These results demonstrate that plant sequences capable of facilitating transcriptional activation can be found and, when fused to DNA‐binding proteins, can enhance gene expression.